Factors and Efforts of Poor Communities in Maintaining Household Resilience - Hanapi, Agustin; Putri, Nadhrah Luthfia (Institut Agama Islam Al-Aziziyah Samalanga, 2024)
Resilience and household integrity is the dream of every couple, but divorce often occurs where economic factors are one of the triggers for the breakdown of family unity. This research uses field research methods with qualitative data types. The findings in this research are, first, the factors of household resilience in poor communities in Rantau Gedang Aceh Singkil Village, which include internal and external factors. Second, the efforts made by the poor community in Rantau Gedang Aceh Singkil Village to maintain the integrity of their household include: remaining grateful, accepting the situation of their partner, helping each other, lightening each other's burdens, supporting each other, trying to continue living a household life together, always praying to Allah, and trying to always carry out the rights and obligations of husband and wife.